Wasaṭīyah Islam: Traditions and Challenges in Southeast Asia - Faiz, Fikri Fahrul; Fadlan, Muhammad Nida' (Studia Islamika, 2022)
In recent years, the rise of intolerant and transnational Islamist groups has challenged the nature of moderate Southeast Asian Muslims. Far away from the center of Islam in Mecca, Muslim communities in the area of Southeast Asia possess diverse traditions within –by encompassing different ethnic groups and languages –and could live together with other religions for centuries. Accordingly, Muslim communities contribute to the stability of this region amidst the acute social unrest in other Muslim worlds, especially in the Middle East and West Africa. Scholars depict the nature of moderate Southeast Asian Muslims as wasaṭīyah (middle path); some call smiling Islam, civil Islam, or flowery Islam. Indonesia, the largest Muslim nation, chose Pancasila as a national consensus –instead of an Islamic state –to accommodate religious plurality.